(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
The presence of biofilm-forming Pseudomonas aeruginosa on noncritical surfaces in a hospital has been attributed to healthcare-associated infections (HAIs) leading to multidrug-resistant (MDR) infections. This study is aimed at identifying the molecular characteristics of Biofilm forming Pseudomonas aeruginosa found on non-critical surfaces in a hospital environment. Samples were collected using the swab technique from different noncritical surfaces surrounding hospitalized patients in different wards namely sphygmomanometers, thermometers, bed rails etc. Bacterial analysis was performed by using conventional microbiological techniques, biochemical tests and Microbact 24E assay. Biofilm forming Pseudomonas aeruginosa were visualized using Crystal Violet staining assay and then estimated by measuring the Optical Density through Spectrophotometer. Four hundred and fifty (450) positive samples of bacterial isolates from noncritical surfaces of six selected wards of the hospital were obtained from one thousand three hundred and fourteen (1314) samples. One hundred and thirty-nine (139) isolates of Pseudomonas spp. were obtained, out of which 115 (82.73%) were identified as biofilm formers. Of these 115 biofilm formers, 83(72.17%) belonged to Pseudomonas aeruginosa, 30(22.09) Pseudomonas fluorescens, 20(17.39%) Pseudomonas putida and 6(5.22%) belongs to Pseudomonas chlorophis. The final characterization of Biofilm forming Pseudomonas aeruginosa isolates was verified by 16S rDNA sequencing. Sequence analysis showed similarity at 99.5% Pearson`s correlation coefficient (r) between 16S rDNA of the representative standard isolate (from gene library) and Biofilm forming Pseudomonas aeruginosa strain obtained from the Tertiary health facility, Federal Medical Centre (FMC), Umuahia. The nucleotide sequence of the experimental isolates expressed genetic mutation which represents the point of involvement of Pel B gene and is involved in the biofilm formation character of Pseudomonas aeruginosa in this study. There is an urgent need to take nosocomial transmission from noncritical surfaces serious in FMC Umuahia.